How Crm Performs Inside Sales Activities In Itc Companies: A Case Study Of Fincons Group, Italy - Arianna, Di Vittorio; Alessandro, Di Gioia Vito (European Scientific Journal, ESJ, 2016)
The aim of this paper is to take a case study of the Fincons Group and examine the in depth activity of the Inside Sales Department. The study presents Fincons Group, which is an IT Consulting Company. Its offices are based in Italy, Switzerland, and England. They are organized into Business Units and are offering concerns to all the different stages of IT applications as well as complex innovation programs. It explains the activities of the Inside Sales Department, specifically the Inside Sales. In detail, Marketing Analysis and Strategy, Marketing Management, and Marketing Research and Metrics have been considered useful to present to the management the guideline for the quantitative and qualitative analysis of customer relationship management programs. Thus, its aim is to optimize the sales process. This study also deals with CRM Salesforce, which is the IT tool used for customer relationship management. In this case, it is possible to analyse the CRM by going over its list of information. Thus, the aim is to give the guideline to quantify the value of customer relationships. In conclusion, the paper highlights the idea of “Holistic CRM”. Specifically, it emphasizes the need for a cross-functional, process-oriented, and calculated approach that positions CRM at a strategic level where business should take precedence over technology.